2021
DOI: 10.21608/ejcm.2021.187676
|View full text |Cite
|
Sign up to set email alerts
|

Learning Styles and Academic Achievement among Medical Students at Ain Shams University: An Experience During COVID-19 Era

Abstract: Background: During the COVID-19 era, the educational system was modified to include blended learning, using a multi-delivery mode to optimize outcome and have the best program delivery cost. Identifying students' learning styles (LS) is an important factor that contributes to scholastic accomplishment, resulting in a more satisfying learning. Objectives: To describe the learning style preferences among medical students at Ain Shams University; to investigate the associations between LS and academic achievement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Every learner has (a) distinctive learning style(s), and one student may adopt single or multiple modes of knowledge acquisition [4]. Studies have shown that when students' learning styles are compatible with the used learning approaches in an educational organization more students' satisfaction, greater achievement and better educational process outcomes are expected [5][6][7][8].…”
Section: Original Article Open Accessmentioning
confidence: 99%
“…Every learner has (a) distinctive learning style(s), and one student may adopt single or multiple modes of knowledge acquisition [4]. Studies have shown that when students' learning styles are compatible with the used learning approaches in an educational organization more students' satisfaction, greater achievement and better educational process outcomes are expected [5][6][7][8].…”
Section: Original Article Open Accessmentioning
confidence: 99%